A comparison of U/Th and rapid‐screen 14C dates from Line Island fossil corals. (12th March 2016) - Grothe, Pamela R.; Cobb, Kim M.; Bush, Shari L.; Cheng, Hai; Santos, Guaciara M.; Southon, John R.; Lawrence Edwards, R.; Deocampo, Daniel M.; Sayani, Hussein R.
Abstract: Time‐consuming and expensive radiometric dating techniques limit the number of dates available to construct absolute chronologies for high‐resolution paleoclimate reconstructions. A recently developed rapid‐screen 14 C dating technique reduces sample preparation time and per sample costs by 90%, but its accuracy has not yet been tested on shallow‐water corals. In this study, we test the rapid‐screen 14 C dating technique on shallow‐water corals by comparing 44 rapid‐screen 14 C dates to both high‐precision 14 C dates and U/Th dates from mid‐ to late‐Holocene fossil corals collected from the central tropical Pacific (2–4°N, 157–160°W). Our results show that 42 rapid‐screen 14 C and U/Th dates agree within uncertainties, confirming closed‐system behavior and ensuring chronological accuracy. However, two samples that grew ∼6500 years ago have calibrated 14 C ages ∼1000 years younger than the corresponding U/Th ages, consistent with diagenetic alteration as indicated by the presence of 15–23% calcite. Mass balance calculations confirm that the observed dating discrepancies are consistent with 14 C addition and U removal, both of which occur during diagenetic calcite recrystallization. Under the assumption that aragonite‐to‐calcite replacement is linear through time, we estimate the samples' true ages using the measured 14 C and U/Th dates and percent calcite values. Results illustrate that the rapid‐screen 14 C dates of Holocene‐aged fossil corals are accurate for samples with less than 2% calcite. Application of this rapid‐screen 14 C method to the fossil coral rubble fields from Kiritimati Island reveal significant chronological clustering of fossil coral across the landscape, with older ages farther from the water's edge. Key Points: Rapid 14 C dating is accurate for Holocene‐aged fossil corals Both 14 C and U/Th coral dates are sensitive to secondary calcite Concordant 14 C and U/Th dates confirm closed system behavior